Safety and Efficacy of Adding Dapagliflozin to Furosemide in Type 2 Diabetic Patients With Decompensated Heart Failure and Reduced Ejection Fraction - Ibrahim, Ayman; Ghaleb, Ramadan; Mansour, Hossam; Hanafy, Amr; Mahmoud, Naggeh M.; Abdelfatah Elsharef, Mohamed; Kamal Salama, Mohamed; Elsaughier, Saud M.; Abdel-Wahid, Lobna; Embarek Mohamed, Mona; Ibrahim, Ahmed K.; Abdel-Galeel, Ahmed (Frontiers in Cardiovascular Medicine, 2020)
Background: Heart failure is the most common cause of hospitalization in elderly patients. It is likely that many of the mechanisms that contribute to reductions in systolic and diastolic function seen in diabetic patients also place them at an increased risk of heart failure. Diuretic therapy, especially loop diuretics, is the usual way of managing congestion, particularly in volume-overloaded patients. Little is known about the beneficial effect of dapagliflozin when added to loop diuretics in managing patients with decompensated heart failure. Aim: To assess the effect of addition of dapagliflozin to furosemide in managing decompensated patient with heart failure and reduced left ventricular ejection fraction. Patients and methods: The study included 100 type 2 diabetic patients who were admitted with decompensated heart failure. The study population was randomly divided into two arms. Serum electrolytes and kidney functions were followed up during hospital stay. Results: With dapagliflozin, there was statistically significant difference between the two groups regarding the change in body weight and body mass index. Also, the diuresis parameters including urine output, total fluid loss, and fluid balance showed statistically significant difference in favor the use of dapagliflozin with no significant change in serum potassium or kidney functions. There was significant improvement in patient-reported dyspnea score with the use of dapagliflozin. Conclusions: Dapagliflozin may provide a new drug option in the treatment of heart failure especially among vulnerable group as diabetics. It has no remarkable effects on serum potassium level and kidney functions.